The seeds of ethnic or tribalistic manifestations in Limpopo: The case of Makhado, Vuwani and Malamulele - Mugovhani, Ndwamato G. (HTS teologiese studies, 2021)
This research article argued that the current conflicts between Vhavenda and Vatsonga, two decades and four years later after the first democratic elections for a new South Africa in 1994, are manifestations of the seeds that were sown by the Voortrekkers since their arrival around the Soutpansberg in the northern parts of South Africa in 1836. Makhado (Louis Trichardt), Vuwani and Malamulele have been embroiled in continuous arguments and counterarguments, advocacies and counter advocacies, including protests, and in some instances, destruction of the essential property. Before then, Vhavenda and Vatsonga used to live alongside each other and even together. In their traditional village settings, there was no discrimination based on language or ethnicity. Through review of early scholarly writings, oral resources garnered from elders and the author’s personal experience, a few episodes were highlighted, and the ramifications thereof were discussed.Contribution: This study also postulated that although the promotion of the tribes’ uniqueness was culturally significant, social cohesion and multiculturalism could have been sustained without institutionalising the segregation laws and demarcations, for these decisions have come back to haunt the present democratic South Africa’s ideals of nation building and social cohesion.